Ice tolerance and metabolite accumulation of herbage crops in Iceland and impact of climate change - Bjarni E. Guðleifsson 1942- (2010)
Ice tolerance of meadow plants and winter cereals was tested in field and also in artificial ice encasement experiments at -2°C in the laboratory. In general the ice tolerance was on the order of: Grass species > clover species > brassicae species, alpine plant and winter cereal species. Within the grasses the ice tolerance of Bering hairgrass and timothy was higher than in other grass species tested, such as cocksfoot and perennial ryegrass. White clover has significantly higher tolerance than red clover, and winter rye is slightly more tolerant than winter wheat and winter barley. In timothy carbohydrates were metabolised during ice encasement, resulting in carbohydrate decrease and accumulation of metabolites. Accumulation of metabolites in grasses, clover and winter cereals during ice encasement at -2°C was also measured in laboratory tests. All plant species tested accumulated CO2 , ethanol and lactate. Timothy and winter wheat also accumulated malate. On a dry weight basis grasses accumulated metabolites to higher concentrations than winter cereals, and in general the more ice tolerant winter rye accumulated metabolites to higher concentrations than winter wheat. Bering hairgrass accumulated CO2 to higher concentrations than timothy, indicating a faster metabolism. The winter temperature in Northern Iceland has increased substantially during recent decades as a result of climate change. Winter damage caused by ice cover is therefore almost eliminated from the agricultural lowland areas. However, there are indications that higher winter temperatures may increase ice damage in alpine areas and harm snow-loving snowbed plants that previously have been protected by a snow layer and therefore have low ice tolerance. Svellþol túnjurta og vetrarkorns og nokkurra fleiri tegunda var metið í vallartilraunum og einnig í vinnustofutilraunum við -2°C. Í heild reyndist svellþolsröðin þessi: Grastegundir > smárategundir> krossblómategundir, fjallaplanta, vetrarkorn. Innan grastegunda voru beringspuntur og ...